2021
DOI: 10.1099/mgen.0.000585
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genomic insights into the epidemiology and virulence of plant pathogenic pseudomonads from Turkey

Abstract: Pseudomonas is a highly diverse genus that includes species that cause disease in both plants and animals. Recently, pathogenic pseudomonads from the Pseudomonas syringae and Pseudomonas fluorescens species complexes have caused significant outbreaks in several agronomically important crops in Tur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…The canonical tripartite TPAI is present in Pseudomonas syringae strains of phylogroup 1, 2, 3, 4, 5, 6 and 10, together with an additional genomic island Rhizobium (RPAI) system present in some P. syringae of phylogroups 2 and 3. Phylogroups 7 and 11 are carrying the Single Pathogenicity Island (SPAI), while the fluorescence (FPAI) system and corrugata (CPAI) island are present only in Pseudomonas fluorescence species complex and Pseudomonas corrugata , respectively (Dillon et al, 2021). The presence of the tripartite mosaic structure codifying for the type III secretion system was confirmed in all the 23 strains under study, together with an additional genomic island of 20 Kb identified as the Rhizobium (RPAI) system (Dillon et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The canonical tripartite TPAI is present in Pseudomonas syringae strains of phylogroup 1, 2, 3, 4, 5, 6 and 10, together with an additional genomic island Rhizobium (RPAI) system present in some P. syringae of phylogroups 2 and 3. Phylogroups 7 and 11 are carrying the Single Pathogenicity Island (SPAI), while the fluorescence (FPAI) system and corrugata (CPAI) island are present only in Pseudomonas fluorescence species complex and Pseudomonas corrugata , respectively (Dillon et al, 2021). The presence of the tripartite mosaic structure codifying for the type III secretion system was confirmed in all the 23 strains under study, together with an additional genomic island of 20 Kb identified as the Rhizobium (RPAI) system (Dillon et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Phylogroups 7 and 11 are carrying the Single Pathogenicity Island (SPAI), while the fluorescence (FPAI) system and corrugata (CPAI) island are present only in Pseudomonas fluorescence species complex and Pseudomonas corrugata , respectively (Dillon et al, 2021). The presence of the tripartite mosaic structure codifying for the type III secretion system was confirmed in all the 23 strains under study, together with an additional genomic island of 20 Kb identified as the Rhizobium (RPAI) system (Dillon et al, 2021). This region was only of 10Kb in Pav MAFF 212061 and totally absent in Pav CC1416 and Pss CRAFRU11 (Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations